Pengaruh Pelatihan dan Gaya Kepemimpinan Terhadap Kinerja Karyawan di PT Adis Dimension Footwear - Siska Amelia; Teguh Kurniyanto (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of training and leadership style on employee performance at PT Adis Dimension Footwear, both partially and simultaneously. The approach used in this study is quantitative with associative research type. Sample determination was carried out using random sampling technique with calculations through the Slovin formula so that a sample size of 80 respondents was obtained. Data processing was carried out through several stages of analysis including validity testing, reliability testing, classical hypothesis testing, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The research results show that training has a positive and significant impact on employee performance. Leadership Style has also been shown to have a positive and significant impact on employee performance. Furthermore, training and leadership Style simultaneously have a positive and significant impact on employee perfomance. These findings indicate that training and leadership style simultaneously have a positive and significant influence on employee performance.